Seebeck Nanoantennas for the Detection and Characterization of Infrared Radiation - Briones, J (Optical Society of American (OSA), 2014)
Arrays of metallic thermocouples in the shape of spiral nanoantennas are proposed as infrared detectors, which use the thermoelectric properties of the metallic interfaces to generate electrical DC signals. The responsivity of these types of antennas is evaluated from both theoretical and numerical perspectives pointing out its potential as infrared sensors. Moreover, the same structures can be used to characterize the state of polarization of the optical near fields with a spatial resolution comparable to the wavelength. © 2014 Optical Society of America.